2017
DOI: 10.1302/1863-2548-11-170012
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical considerations in slipped capital femoral epiphysis and insights into prophylactic fixation

Abstract: PurposeSlipped capital femoral epiphysis (SCFE) is a deformity of the proximal femur secondary to widened and unstable physis. In stabilising the slip, gold standard treatments stop growth and involve premature physeal closure, which prevents the remodelling of the acquired deformity and creates a leg length discrepancy that may be significant in younger patients.MethodsWe measured the impact of placing threaded screws across the proximal femoral physis by measuring the centre-trochanteric distance (CTD) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Finite element analysis has been previously used in several studies to investigate the influence of growth plate characteristics and shear loads on development and progression of SCFE . Our findings are in line with those by Fishkin et al who demonstrated with a finite element study that the peak stress distribution is concentrated in the posterior part of the proximal femoral physis.…”
Section: Discussionsupporting
confidence: 90%
“…Finite element analysis has been previously used in several studies to investigate the influence of growth plate characteristics and shear loads on development and progression of SCFE . Our findings are in line with those by Fishkin et al who demonstrated with a finite element study that the peak stress distribution is concentrated in the posterior part of the proximal femoral physis.…”
Section: Discussionsupporting
confidence: 90%
“…Also, it has been suggested that increasing the height of the growth plate unlocks the interdigitating secondary mammillary processes (Speer & Braun, 1985) to reduce resistance to shear. Radiologists have reported widening of the growth plate accompanying slips, which may be subtle or as much as a five‐fold increase in thickness (Khaladkar et al, 2015; Leblanc, Bellemore, et al, 2017; Tresoldi, Modesti, et al, 2017), although it is unclear if this widening is a contributing factor to the slip or a consequence thereof. The thickness or height of the growth plate varies with age, rate of growth and endocrine function.…”
Section: Discussionmentioning
confidence: 99%
“…The premature physeal closure leads to modifications of the epiphyseal–metaphyseal complex which itself becomes a cause of impingement [ 30 , 32 ]. To avoid this complication, it is necessary to use a type of in situ fixation device which allows continued physeal growth [ 13 , 18 21 ]. Immediate arthroscopic osteoplasty as Leunig et al (2010) [ 11 ] proposed might not be necessary if the initial treatment is done using such a device.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Menelaus (1991) [ 12 ], the femoral neck grows at an estimated rate of 4.0 mm/year. In younger patients, premature closure of the physis risks development of a short femoral neck, producing a short lever arm and a high-riding trochanter with progressive deformity of the epiphyseal–metaphyseal complex of the proximal femur, leading to premature osteoarthritis [ 13 , 14 ]. A standard screw fixation associated with an osteochondroplasty may then cause a premature closure of the physis and consequent deformity of the head-neck junction associated with an overgrowth of the great trochanter.…”
Section: Introductionmentioning
confidence: 99%